2020
DOI: 10.1590/1414-431x20209628
|View full text |Cite
|
Sign up to set email alerts
|

Ophiopogonin D of Ophiopogon japonicus ameliorates renal function by suppressing oxidative stress and inflammatory response in streptozotocin-induced diabetic nephropathy rats

Abstract: Ophiopogonin D (OP-D) is the principal pharmacologically active ingredient from Ophiopogon japonicas, which has been demonstrated to have numerous pharmacological activities. However, its protective effect against renal damage in streptozotocin (STZ)-induced diabetic nephropathy (DN) rats remains unclear. The present study was performed to investigate the protective effect of OP-D in the STZ-induced DN rat model. DN rats showed renal dysfunction, as evidenced by decreased serum albumin and creatinine clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
(38 reference statements)
2
15
0
Order By: Relevance
“…[34,35] These inflammatory cytokines further start the production of a chemotactic factor in the renal tissues, which induced the infiltration of the inflammatory cells. [36] Finally, this process is involved in the expansion of renal injury. TNF-α boosts the chemotactic factors and inflammatory factors, they are involved in the expansion of inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…[34,35] These inflammatory cytokines further start the production of a chemotactic factor in the renal tissues, which induced the infiltration of the inflammatory cells. [36] Finally, this process is involved in the expansion of renal injury. TNF-α boosts the chemotactic factors and inflammatory factors, they are involved in the expansion of inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…OPD exerted anti-obesity effect on HFD-induced metabolic syndrome mice through regulating gut microbiota, precisely, by reducing Firmicutes/Bacteroidetes ratios and endotoxin-bearing Proteobacteria levels ( Chen S. et al, 2018 ). In addition, OPD played a protective role against renal damage in STZ-induced diabetic nephropathy through suppressing oxidative damage as evidence by the decreased level of MDA and increased activity of SOD, GSH, CAT, along with inflammatory response by reducing pro-inflammatory cytokines (IL-6, IL-1β) ( Qiao et al, 2020 ). Ruscogenin was also reported can improve diabetic nephropathy ( Lu et al, 2014 ).…”
Section: Pharmacological Properties Of Liriopogonsmentioning
confidence: 99%
“…Ophiopogonin D (OP-D) is a steroidal glycoside from Ophiopogon japonicus. Recent studies have shown that OP-D is effective in diseases such as diabetic myocardial injuries , obesity (Chen Y. et al, 2018), osteoporosis (Huang et al, 2015), atopic dermatitis (An et al, 2020), and has a distinct anti-oxidant and anti-inflammatory effect (Ma et al, 2018;Qiao and Jiao 2020). OP-D has also been shown to have anti-cancer effects by controlling various signaling pathways in lung cancer (Lee et al, 2018a;Lee et al, 2018b), breast cancer (Zang et al, 2016;Zhu, Wang, and Chen 2020), and prostate cancer (Lu et al, 2018;Lu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%